Water Relations of Xerophilic Fungi Isolated from Prunes - Pitt, J. I. (Appl Microbiol, 1968)
The predominant spoilage fungi of dried and high-moisture prunes were members of the Aspergillus glaucus group and Xeromyces bisporus. Chrysosporium spp. were also important. At the mean pH of prune flesh (3.8) and at 25 C, X. bisporus grew at water activities (a(w)) down to 0.605, and Chrysosporium fastidium grew to 0.686. Germination was always followed by growth, but within the 120-day incubation period, the minimum a(w) permitting asexual sporulation was usually higher than that permitting germination. Sexual sporulation often required an even higher a(w). The water requirements of aspergilli were appreciably greater at this pH than near neutrality, no species germinating below 0.738 a(w). This was probably a consequence of a high spore-death rate during incubation at low a(w) and pH.